The Importance of living - Lin, Yutang (Melbourne William Heinemann LTD., 1955)
A wry, witty antidote to the dizzying pace of the modern world. Lin Yutang's prescription is the classic Chinese philosophy of life: revere inaction as much as action, invoke humor to maintain a healthy attitude, and never forget that there will always be plenty of fools around who are willing--indeed, eager--to be busy, to make themselves useful, and to exercise power while you bask in the simple joy of existence. At a time when we're overwhelmed with wake-up calls, here is a refreshing, playful reminder to savor life's simple pleasures
Include Appendix and Index
Keywords: Life -- Conduct of life